Construction of LGBT People in Digital Media (Framing Analysis of CNN Indonesia News) - Teguh Agum Pratama; Safira Putri Miranti; Yola Amanda; Arya Dwi Putra; Muzhirah Muzhirah (University of Science and Computer Technology, 2023)
This article aims to analyze media perceptions in the coverage of Medan Mayor Boby Nasution on the rejection of LGBT in Medan City. LGBT should not have happened in Indonesia, especially in the city of Medan because it has violated Pancasila, cultural and religious norms that have become legal provisions in Indonesia. This study implements a qualitative descriptive method with framing analysis techniques in the form of documentation and media observations. The results include: the movement of the LGBT group does not have the space or scope to accept it in Indonesia, because its existence itself has been banned by regulations and applicable social norms, because in essence this group only brings a disaster of deviation to teenagers who have absolutely no element of benefit for the people.